The necessity to think. Philosophy as an activity - Bedoya Giraldo, Hubed (Estudios de Filosofía, 1993)
Many and dissimilar explanations have been proposed to account for what seems to be an evident phenomenon in our Latin American cultural sphere: the absence of Philosophy. Some conceptions simply assure the non-existence and even the impossibility of a form of "philosophical thought" in this part of the cultural world, while others affirm the impossibility of speaking of geographical compartments in a "doing" that is intended, by definition, universal in nature.